2012
DOI: 10.5551/jat.12757
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function Influences Serum Apolipoprotein B-48 Levels in Patients with Thyroid Disease

Abstract: Aim: Apolipoprotein B-48 (apoB-48) is a major apolipoprotein of intestine-derived chylomicrons (CM) and CM remnants (CMR).Clinically overt hypothyroidism (OH) has been associated with premature and accelerated coronary atherosclerosis. To clarify the clinical significance of apoB-48 measurement in patients with thyroid disease, we investigated the correlations between the serum apoB-48 level and thyroid hormones. Methods: From outpatients of Osaka University Hospital, patients with OH, subjects with subclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…TH can also reduce the production of ApoB48 and ApoB100, thus reducing the production of VLDL and chylomicron (CM) ( 43 , 44 ). Moreover, ApoB48 levels are negatively correlated to TH ( 45 ). Overall, the reduction of TH inhibits cholesterol synthesis via HMGCR but promotes the absorption of cholesterol through NPC1L1 and reduces catabolism through β-oxidation.…”
Section: The Mechanism Of Dyslipidemia In Hypothyroidismmentioning
confidence: 99%
See 2 more Smart Citations
“…TH can also reduce the production of ApoB48 and ApoB100, thus reducing the production of VLDL and chylomicron (CM) ( 43 , 44 ). Moreover, ApoB48 levels are negatively correlated to TH ( 45 ). Overall, the reduction of TH inhibits cholesterol synthesis via HMGCR but promotes the absorption of cholesterol through NPC1L1 and reduces catabolism through β-oxidation.…”
Section: The Mechanism Of Dyslipidemia In Hypothyroidismmentioning
confidence: 99%
“…It has been found that TSH increased the phosphorylation of perilipin and hormone-sensitive lipase (HSL) to increase lipolysis, and circulating FFA increased significantly after TSH injection in vitro studies ( 53 ). Also, TSH could stimulate the increase of ApoB ( 31 , 45 ). So, we could speculate that TSH is capable as a stand-alone hormone to produce a physiological response on lipid metabolism and have an effect independent of TH.…”
Section: The Mechanism Of Dyslipidemia In Hypothyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, studies have also shown the impaired activity of hepatic lipidosis (HL) in hypothyroidism patients may be also related to the excessive accumulation of TRL [72]. Another research found that the transferring of TG to HDL was significantly impaired in patients with subclinical hypothyroidism, indicating that although intra-vascular metabolism of triglyceride-rich lipoproteins was normal, patients with subclinical hypothyroidism showed abnormalities in HDL metabolism which could be improved by levothyroxine treatment and achievement of euthyroidism [73].…”
Section: Functions Of Thyroid Hormones In Modulating Serum Tg Metabolismmentioning
confidence: 99%
“…Conversely, Mugii et al [12] suggest that both hypothyroidism and subclinical hypothyroidism accelerate the accumulation of chylomicrons and chylomicron remnants. They measured apolipoprotein B-48 (apoB-48) and identified a positive correlation with TSH and a negative correlation with free thyroxine and triiodothyronine.…”
mentioning
confidence: 97%